Quasi-solid electrolyte for nickel-zinc battery and nickel-zinc battery thereof
By using quasi-solid electrolytes in nickel-zinc batteries, the problems of electrolyte leakage and high cost are solved, and the safety and durability of the battery are improved, and it is suitable for high-end electrical equipment.
Patent Information
- Application Number
- CN202510203300.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-07-04
AI Technical Summary
The existing nickel-zinc batteries use alkaline liquid electrolytes to cause the risk of electrolyte leakage and high manufacturing cost.
A quasi-solid electrolyte for nickel-zinc battery is adopted, including a quasi-solid matrix, alkaline compounds, additives and solvents. The additives include conductive agents, insulating substances, fibers and zinc-containing substances to form an electrolyte that can conduct ions and isolate positive and negative electrodes.
It effectively eliminates the risk of electrolyte leakage, reduces preparation costs, improves the safety and reliability of the battery, enhances the durability and scope of application of the battery, and is especially suitable for high-end electrical equipment.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nickel-zinc batteries, and particularly to a quasi-solid electrolyte for nickel-zinc batteries and a nickel-zinc battery using the same. Background Art
[0002] Most of the commercially available nickel-zinc cylindrical batteries on the market currently use alkaline liquid electrolytes, known as liquid batteries. However, as the battery service life extends, the following problems may occur in liquid batteries: First, there may be a risk of electrolyte leakage when using alkaline liquid electrolytes, resulting in corrosion or pollution after the battery comes into contact with the electrical equipment. Second, in the electrolyte of liquid batteries, the concentration of alkaline liquid electrolytes is usually relatively high, generally between 5 - 8 mol / L. This not only increases the complexity of the electrolyte during preparation, storage, and transportation, but also raises the production cost. Third, the separator material used in liquid batteries usually has a high cost in order to have good alkali absorption performance, which also exacerbates the increase in the overall manufacturing cost of nickel-zinc batteries. Summary of the Invention
[0003] In view of the problems that existing nickel-zinc batteries using alkaline liquid electrolytes have the risk of electrolyte leakage and high overall manufacturing cost of the batteries, the present application provides a quasi-solid electrolyte for nickel-zinc batteries and a nickel-zinc battery using the same.
[0004] In the first aspect, the present invention provides a quasi-solid electrolyte for nickel-zinc batteries, including the following parts by weight: 5 - 10 parts of a quasi-solid matrix, 30 - 35 parts of an alkaline compound, 2 - 8 parts of an additive, and 57 - 63 parts of a solvent. The additive includes two or more of a conductive agent, an insulating substance, a fiber, and a zinc-containing substance.
[0005] Preferably, the insulating substance includes one or more of silicon oxide, wollastonite, and asbestos.
[0006] Preferably, the fiber includes one or more of aluminum silicate fiber, nylon 66 fiber, carbon fiber, acetate fiber, and polyvinyl alcohol fiber.
[0007] Preferably, the zinc-containing substance includes one or more of zinc oxide, magnesium zincate, zinc copper alloy, zinc magnesium alloy, and zinc aluminum alloy.
[0008] Preferably, the diameters of the zinc copper alloy, the zinc magnesium alloy, and the zinc aluminum alloy are all 220 - 400 mesh.
[0009] Preferably, the conductive agent includes one or more of Ketjen black, carbon black, graphene, carbon nanotubes, and graphite.
[0010] Preferably, the thickness of the quasi-solid electrolyte is 0.5-2 mm; and / or, the ionic conductivity of the quasi-solid electrolyte is 50-120 mS / cm.
[0011] Preferably, the additive is composed of a conductive agent, an insulating substance, a fiber, and a zinc-containing substance. In the additive, the mass ratio of the conductive agent, the insulating substance, the fiber, and the zinc-containing substance is (1-2):(1-3):(1-3):(1-2).
[0012] Preferably, the quasi-solid matrix includes one or more of polyvinyl alcohol, sodium carboxymethyl cellulose, polyacrylic acid, and polyacrylamide; The alkaline compound includes one or more of KOH, NaOH, and LiOH; The solvent is deionized water.
[0013] In a second aspect, the present application provides a nickel-zinc battery, including a positive electrode, a negative electrode, and the above-mentioned quasi-solid electrolyte, and the quasi-solid electrolyte is disposed between the positive electrode and the negative electrode.
[0014] The quasi-solid electrolyte for nickel-zinc batteries provided by the present application has the following effects: 1) By using the quasi-solid electrolyte for nickel-zinc batteries provided by the present application, compared with the liquid electrolyte, the risk caused by electrolyte leakage during long-term use of the battery is effectively eliminated, and the safety and reliability of the battery are enhanced; 2) The quasi-solid electrolyte has better stability in production, storage, and transportation. Compared with the high-concentration liquid electrolyte, the production process is simplified and the preparation cost is reduced; 3) The quasi-solid electrolyte for nickel-zinc batteries provided by the present application does not require the use of a strong alkali-absorbing separator material, reducing the dependence on the alkali-absorbing separator material and further reducing the overall manufacturing cost of the nickel-zinc battery; 4) The quasi-solid electrolyte for nickel-zinc batteries provided by the present application solves the hidden dangers in the daily use of traditional nickel-zinc batteries using liquid electrolytes, improves the durability and application range of the battery, and is especially suitable for the market demand of high-end electrical equipment; 5) The quasi-solid electrolyte for nickel-zinc batteries provided by the present application contains two or more of a conductive agent, an insulating substance, a fiber, and a zinc-containing substance in the additive, which helps to improve the battery cycle life and improve the high-temperature storage performance of the battery. Specific Embodiments
[0015] In order to make the objectives, technical solutions, and advantages of the present invention clearer, the following further describes the present invention in detail with reference to embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0016] In order to illustrate the technical solution of the present invention, the following is illustrated by specific embodiments.
[0017] In a first aspect, the present application provides a quasi-solid electrolyte for a nickel-zinc battery, comprising the following parts by weight: 5 to 10 parts of a quasi-solid matrix, 30 to 35 parts of an alkaline compound, 2 to 8 parts of an additive, and 57 to 63 parts of a solvent, wherein the additive comprises two or more of a conductive agent, an insulating substance, a fiber, and a zinc-containing substance.
[0018] Specifically, the quasi-solid matrix can provide mechanical support and shape retention for the quasi-solid electrolyte, so that the electrolyte does not flow randomly like a liquid electrolyte, preventing the risk of electrolyte leakage.
[0019] The conductive agent can enhance the ionic conductivity of the quasi-solid electrolyte; the insulating substance helps to reduce the polarization of the zinc negative electrode, reduce the battery internal resistance, and increase the specific capacity of the active material; the fiber can relieve the deformation of the negative electrode of the nickel-zinc battery and enhance the flexibility of the quasi-solid electrolyte; the zinc-containing substance can reduce the dissolution of zinc in the negative electrode, reduce the degree of deformation of the zinc negative electrode, and reduce the capacity attenuation.
[0020] In the quasi-solid electrolyte for a nickel-zinc battery, the additive is 2 to 8 parts, which helps to improve the room-temperature cycle performance and high-temperature storage performance of the battery. If the content of the additive is less than 2 parts, the high-temperature storage capacity retention rate of the battery decreases, the high-temperature storage capacity recovery rate decreases, and the room-temperature cycle capacity retention rate of the battery decreases; if the content of the additive is higher than 8 parts, it will cause too much additive in the solid electrolyte, which will reduce the conductivity, interfere with the electrode reaction, exacerbate self-discharge, weaken the thermal stability, and damage the performance of the nickel-zinc battery. In the quasi-solid electrolyte for a nickel-zinc battery, the content of the additive can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, etc.
[0021] The quasi-solid electrolyte for a nickel-zinc battery provided by the present application has the following effects: 1) By using the quasi-solid electrolyte for nickel-zinc batteries provided in this application, compared with liquid electrolytes, the risk caused by electrolyte leakage during long-term use of the battery is effectively eliminated, and the safety and reliability of the battery are enhanced; 2) The quasi-solid electrolyte has better stability in production, storage and transportation. Compared with high-concentration liquid electrolytes, the production process is simplified and the preparation cost is reduced; 3) The quasi-solid electrolyte for nickel-zinc batteries provided in this application does not require the use of strongly alkaline-absorbing separator materials, reducing the dependence on alkaline-absorbing separator materials and further reducing the overall manufacturing cost of nickel-zinc batteries; 4) The quasi-solid electrolyte for nickel-zinc batteries provided in this application solves the hidden dangers in the daily use of traditional nickel-zinc batteries using liquid electrolytes, improves the durability and application range of the battery, and is especially suitable for the market demand of high-end electrical equipment; 5) The quasi-solid electrolyte for nickel-zinc batteries provided in this application contains additives including two or more of conductive agents, insulating substances, fibers, and zinc-containing substances, which helps to improve the battery cycle life and improve the high-temperature storage performance of the battery.
[0022] In some preferred embodiments, the additives include three or four of conductive agents, insulating substances, fibers, and zinc-containing substances.
[0023] Specifically, the additives contain at least three of the above types. The additives interact with each other, which is more conducive to reducing the negative electrode polarization, reducing the battery internal resistance, reducing the battery capacity attenuation, improving the battery cycle life, and improving the high-temperature storage performance of the battery.
[0024] In some embodiments, the insulating substance includes one or more of silicon oxide, wollastonite, and asbestos.
[0025] Specifically, asbestos contains silicon and magnesium elements. The insulating substance includes one or more of silicon oxide, wollastonite, and asbestos; all of the above types contain silicon elements, which helps to reduce the polarization of the zinc negative electrode, reduce the battery internal resistance, and increase the specific capacity of the active material, improving the battery cycle life and high-temperature storage performance.
[0026] In some embodiments, the fiber includes one or more of aluminum silicate fiber, nylon 66 fiber, carbon fiber, acetate fiber, and polyvinyl alcohol fiber.
[0027] Specifically, aluminum silicate fiber, nylon 66 fiber, carbon fiber, acetate fiber, and polyvinyl alcohol fiber not only contain substances that can relieve the deformation of the negative electrode of the nickel-zinc battery, but also can be evenly embedded in the quasi-solid electrolyte network, enhancing the flexibility of the quasi-solid electrolyte.
[0028] In some embodiments, the zinc-containing substance includes one or more of zinc oxide, magnesium zincate, copper alloy, zinc magnesium alloy, and zinc aluminum alloy.
[0029] Specifically, the negative electrode of the nickel-zinc battery is prone to dissolution and corrosion in an alkaline environment. Adding a zinc-containing substance to the quasi-solid electrolyte can reduce the dissolution of zinc in the negative electrode, reduce the deformation degree of the zinc negative electrode, and reduce the capacity attenuation.
[0030] In some embodiments, the diameters of the zinc-copper alloy, the zinc-magnesium alloy, and the zinc-aluminum alloy are all 220-400 mesh.
[0031] Specifically, the diameters of the zinc-copper alloy, the zinc-magnesium alloy, and the zinc-aluminum alloy can be in the following ranges: 220-250 mesh, 250-280 mesh, 280-300 mesh, 300-320 mesh, 320-350 mesh, or 350-400 mesh.
[0032] In some embodiments, the conductive agent includes one or more of Ketjen black, carbon black, graphene, carbon nanotubes, and graphite.
[0033] Specifically, the ionic conductivity of the quasi-solid electrolyte is smaller than that of the liquid electrolyte. Adding an additive conductive agent to the quasi-solid electrolyte can enhance the ionic conduction ability in the quasi-solid electrolyte and increase the ionic conductivity of the quasi-solid electrolyte.
[0034] In some embodiments, the additive is composed of a conductive agent and an insulating substance. In the additive, the mass percentage content of the conductive agent is less than 50%.
[0035] In some embodiments, the additive is composed of a conductive agent and a fiber. In the additive, the mass percentage content of the conductive agent is less than 50%.
[0036] In some embodiments, the additive is composed of a conductive agent and a zinc-containing substance. In the additive, the mass percentage content of the conductive agent is greater than 50%.
[0037] In some embodiments, the additive is composed of an insulating substance and a fiber. In the additive, the mass percentage content of the insulating substance is greater than 50%.
[0038] In some embodiments, the additive is composed of an insulating substance and a zinc-containing substance. In the additive, the mass percentage content of the insulating substance is greater than 50%.
[0039] In some embodiments, the additive is composed of a fiber and a zinc-containing substance. In the additive, the mass percentage content of the fiber is less than 50%.
[0040] In some embodiments, the additive is composed of a conductive agent, an insulating substance, and a fiber. In the additive, the mass percentage content of the fiber is greater than 30%, and the mass percentage content of the insulating substance is greater than 30%.
[0041] In some embodiments, the additive is composed of a conductive agent, an insulating substance, and a zinc-containing substance. In the additive, the mass percentage content of the insulating substance is greater than 30%, and the mass percentage content of the zinc-containing substance is less than 30%.
[0042] In some embodiments, the additive is composed of an insulating substance, fibers, and a zinc-containing substance. In the additive, the mass percentage content of the fibers is greater than 30%, and the mass percentage content of the zinc-containing substance is less than 30%.
[0043] In some embodiments, the thickness of the quasi-solid electrolyte is 0.5 - 2 mm.
[0044] Specifically, when the thickness of the quasi-solid electrolyte is within the range of 0.5 - 2 mm, the thickness is relatively small, the transport path of ions in the quasi-solid electrolyte is relatively short, which improves the ion conduction efficiency; at the same time, it has good flexibility and strength, plays a supporting role, has a good contact area with the positive and negative electrodes, reduces the interfacial impedance, and improves the overall performance of the battery. Specifically, the thickness of the quasi-solid electrolyte can be 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.2 mm, 1.5 mm, 1.7 mm, 1.8 mm, or 2.0 mm, etc.
[0045] It can be understood that compared with liquid batteries, in solid-state batteries, the quasi-solid electrolyte can act as both an electrolyte and a separator to prevent the positive and negative electrodes from contacting, and the preparation cost of the battery is relatively low.
[0046] In some embodiments, the ionic conductivity of the quasi-solid electrolyte is 50 - 120 mS / cm.
[0047] Specifically, when the ionic conductivity of the quasi-solid electrolyte is within the range of 50 - 120 mS / cm, the ionic conductivity is high, which is beneficial to improving the cycle life of the battery and improving the battery electrical performance.
[0048] In some embodiments, the quasi-solid matrix includes one or more of polyvinyl alcohol, sodium carboxymethyl cellulose, polyacrylic acid, and polyacrylamide.
[0049] The quasi-solid matrix includes the above types, which is beneficial to forming a three-dimensional network structure with certain mechanical strength and flexibility, playing a good supporting role, providing a transport channel for zinc ions, having good contact with the positive and negative electrode interfaces, and reducing the interfacial resistance; at the same time, uniformly distributing the alkaline compound, solvent, and additive throughout the quasi-solid electrolyte system.
[0050] In some embodiments, the alkaline compound includes one or more of KOH, NaOH, and LiOH.
[0051] The alkaline compound includes the above types and is used as an alkaline electrolyte, dissolved in a solvent and filled in the quasi-solid electrolyte system to achieve ion conduction.
[0052] In some embodiments, the solvent is deionized water.
[0053] The solvent is deionized water, which dissolves alkaline compounds, additives, etc., enabling the alkaline electrolyte to exist in ionic form and move freely, having an important impact on ion transport and battery reactions.
[0054] In some embodiments, the additive is composed of a conductive agent, an insulating substance, fibers, and a zinc-containing substance. In the additive, the mass ratio of the conductive agent, the insulating substance, the fibers, and the zinc-containing substance is (1 - 2):(1 - 3):(1 - 3):(1 - 2).
[0055] Specifically, the additive is composed of a conductive agent, an insulating substance, fibers, and a zinc-containing substance, and satisfies the mass ratio range of the conductive agent, the insulating substance, the fibers, and the zinc-containing substance of (1 - 2):(1 - 3):(1 - 3):(1 - 2), which is beneficial to the interaction of the four additives, more effectively reducing the negative electrode polarization, reducing the battery internal resistance, reducing the battery capacity attenuation, increasing the battery cycle life, and improving the battery high-temperature storage performance.
[0056] Further preferably, the quasi-solid electrolyte includes the following parts by weight: 6 parts of quasi-solid matrix, 30 parts of alkaline compound, 6 parts of additive, and 58 parts of solvent.
[0057] In a second aspect, the present application provides a nickel-zinc battery, including a positive electrode sheet, a negative electrode sheet, and the above-mentioned quasi-solid electrolyte, and the quasi-solid electrolyte is disposed between the positive electrode and the negative electrode.
[0058] Specifically, the quasi-solid electrolyte is disposed between the positive electrode and the negative electrode. The quasi-solid electrolyte can not only be used as an electrolyte but also as a separator to prevent the positive and negative electrodes from contacting.
[0059] The nickel-zinc battery provided by the present application includes a quasi-solid electrolyte disposed between the positive electrode and the negative electrode, avoiding the occurrence of battery leakage, while reducing the battery manufacturing cost, improving the battery cycle life and high-temperature storage performance, increasing the battery durability and application range, and is especially suitable for high-end markets with high requirements for battery performance and stability.
[0060] The positive electrode sheet and the negative electrode sheet in the nickel-zinc battery are of the prior art.
[0061] If the positive electrode plate includes a positive electrode current collector and a positive electrode coating provided on the surface of the positive electrode current collector, the positive electrode coating includes a positive electrode active material, a positive electrode additive, and a positive electrode binder. Regarding the mixing ratio among the positive electrode active material, the positive electrode additive, and the positive electrode binder, the present application does not make any limitation, and reference can be made to the prior art.
[0062] The positive electrode active material includes Ni(OH)2, and the positive electrode additives include ZnO, CoO, Ni powder, Ca(OH)2, Y2O3, Yb2O3, graphite, etc.
[0063] The positive electrode binder includes CMC, PTFE, etc.
[0064] The negative electrode plate includes a negative electrode current collector and a negative electrode coating provided on the surface of the negative electrode current collector.
[0065] The negative electrode coating includes a negative electrode active material, a negative electrode additive, a conductive agent, a thickening agent, a dispersing agent, and a negative electrode binder. Regarding the negative electrode active material, the negative electrode additive, the conductive agent, the thickening agent, the dispersing agent, and the negative electrode binder; their mixing ratios are not limited in the present application, and reference can be made to the prior art.
[0066] The negative electrode active material includes zinc and zinc oxides.
[0067] The negative electrode additives include In2O3, Bi2O3, Al2O3, etc.
[0068] The thickening agent includes one or more of sodium carboxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl methyl cellulose.
[0069] The conductive agent includes one or more of activated carbon, conductive carbon black, carbon nanotubes, graphene, and vapor-grown carbon fibers.
[0070] The dispersing agent includes one or more of sodium polyacrylate, potassium polyacrylate, and polyacrylamide.
[0071] The negative electrode binder includes one or more of styrene-butadiene rubber and polytetrafluoroethylene.
[0072] Example 1 This example is used to illustrate a quasi-solid electrolyte for a nickel-zinc battery and a nickel-zinc battery disclosed by the present invention, and includes the following operating steps: 1) Prepare the positive electrode: Mix the following substances evenly by stirring according to a mass ratio of 86% Ni(OH)2, 1 wt% ZnO, 3 wt% CoO, 4 wt% Ni powder, 2 wt% Ca(OH)2, 2 wt% Y2O3, 1 wt% Yb2O3, 0.5 wt% CMC, and 0.5 wt% PTFE, then coat them on the positive electrode current collector, and obtain the positive electrode of the nickel-zinc battery through processes such as rolling, softening, and cutting.
[0073] 2) Preparation of the negative electrode: (1) Take 1.5 wt% conductive agent carbon black, 0.32 wt% thickening agent sodium carboxymethyl cellulose, and 1.5 wt% dispersant sodium polyacrylate, mix them evenly, then add 0.05 wt% In2O3, 2.8 wt% Bi2O3, and 4 wt% Al2O3, stir for 30 min, then add 1.5 wt% Ca(OH)2 and stir for 30 min. After mixing evenly, add 61 wt% ZnO and 27 wt% Zn in three portions, mix evenly again, and finally add 0.33 wt% binder styrene-butadiene rubber and mix evenly again to obtain the negative electrode slurry. (2) Coat the negative electrode slurry onto the inclined drawn tin-coated copper mesh current collector, roll, soften, and cut to obtain the negative electrode of the nickel-zinc battery.
[0074] 3) Preparation of the quasi-solid-state electrolyte: S1: Prepare raw materials In the quasi-solid-state electrolyte, there are 6 parts of the quasi-solid-state matrix, 30 parts of the alkaline compound, 6 parts of the additive, and 58 parts of the solvent.
[0075] Among them, the quasi-solid-state matrix is selected from polyvinyl alcohol and sodium carboxymethyl cellulose, and the mass ratio of polyvinyl alcohol to sodium carboxymethyl cellulose is 4:1; The alkaline compound is selected as potassium hydroxide; The additive is selected from Ketjenblack, silicon oxide, aluminum silicate fiber, and magnesium zincate, and the mass ratio of Ketjenblack, silicon oxide, aluminum silicate fiber, and magnesium zincate in the additive is 1:2:2:1; the particle size of magnesium zincate is 280 - 300 mesh.
[0076] The solvent is deionized water.
[0077] S2: Preparation of the quasi-solid-state electrolyte Add 6 parts of the quasi-solid-state matrix in step S1 to 58 parts of water, stir for 30 min, then add 6 parts of the additive in step S1 and stir for 10 min; after slowly adding 30 parts of the alkaline compound in step S1, heat the system to 60 °C and stir for 2 h to obtain the mixed slurry.
[0078] Transfer the mixed slurry to a mold, level it, cool it to room temperature (25 ± 5 °C), and then cut to obtain the quasi-solid-state electrolyte.
[0079] The obtained quasi-solid-state electrolyte has a thickness of 1 mm.
[0080] 4) Preparation of the nickel-zinc battery Stack the positive electrode obtained in step 1), the quasi-solid-state electrolyte obtained in step 3), and the negative electrode obtained in step 2) in sequence, with the quasi-solid-state electrolyte in the middle of the positive and negative electrodes, prepare the battery core, and perform processes such as encapsulation, standing, formation, and shaping to obtain the nickel-zinc battery.
[0081] Example 2 Most steps in this embodiment are the same as those in Embodiment 1. The difference lies in the types of additives in Step S1. The types of additives in Embodiment 2 are Ketjen black, wollastonite, aluminum silicate fiber, and magnesium zincate. In the additives, the mass ratio of Ketjen black, wollastonite, aluminum silicate fiber, and magnesium zincate is 2:1:3:2. The rest is the same as in Embodiment 1.
[0082] Embodiment 3 Most steps in this embodiment are the same as those in Embodiment 1. The difference lies in the types of additives in Step S1. The types of additives in Embodiment 3 are graphene, silicon oxide, aluminum silicate fiber, and magnesium zincate. In the additives, the mass ratio of graphene, silicon oxide, aluminum silicate fiber, and magnesium zincate is 1.5:3:1:1.5. The rest is the same as in Embodiment 1.
[0083] Embodiment 4 Most steps in this embodiment are the same as those in Embodiment 3. The difference lies in the types of additives in Step S1. The types of additives in Embodiment 4 are graphene, silicon oxide, aluminum silicate fiber, and zinc aluminum alloy. The diameter size of the zinc aluminum alloy is 325 mesh; in the additives, the mass ratio of graphene, silicon oxide, aluminum silicate fiber, and zinc aluminum alloy is 1:2.5:2:1. The rest is the same as in Embodiment 1.
[0084] Embodiment 5 Most steps in this embodiment are the same as those in Embodiment 1. The difference lies in that the thickness of the quasi-solid electrolyte prepared in Step S2 is 1.2 mm.
[0085] Embodiment 6 Most steps in this embodiment are the same as those in Embodiment 1. The difference lies in that the thickness of the quasi-solid electrolyte prepared in Step S2 is 2.0 mm.
[0086] Embodiment 7 Most steps in this embodiment are the same as those in Embodiment 1. The difference lies in that the thickness of the quasi-solid electrolyte prepared in Step S2 is 2.3 mm.
[0087] Embodiment 8 Most steps in this embodiment are the same as those in Embodiment 1. The difference lies in that the thickness of the quasi-solid electrolyte prepared in Step S2 is 0.2 mm.
[0088] Embodiment 9 Most steps in this embodiment are the same as those in Embodiment 1. The difference lies in that polyvinyl alcohol is selected as the quasi-solid matrix in Step S1. The rest is the same as in Embodiment 1.
[0089] Embodiment 10 Most of the steps in this embodiment are the same as those in Embodiment 1. The difference is that in step S1, the quasi-solid matrix is sodium carboxymethyl cellulose, and the rest is the same as in Embodiment 1.
[0090] Embodiment 11 Most of the steps in this embodiment are the same as those in Embodiment 1. The difference is that in step S1, the types of additives are different. The additives are carbon nanotubes, asbestos, polyvinyl alcohol fibers, and zinc-copper alloy; the mass ratio of carbon nanotubes, asbestos, polyvinyl alcohol fibers, and zinc-copper alloy in the additives is 1:2:2:1; the rest is the same as in Embodiment 1. The diameter of the zinc-copper alloy is 350 - 400 mesh.
[0091] Embodiment 12 Most of the steps in this embodiment are the same as those in Embodiment 1. The difference is that in step S1, the mass ratio of Ketjen black, silicon oxide, aluminum silicate fiber, and magnesium zincate is 0.5:0.5:3:2. The rest is the same as in Embodiment 1.
[0092] Embodiment 13 Most of the steps in this embodiment are the same as those in Embodiment 1. The difference is that in step S1, the mass ratio of Ketjen black, silicon oxide, aluminum silicate fiber, and magnesium zincate is 3:4:3:2. The rest is the same as in Embodiment 1.
[0093] Embodiment 14 Most of the steps in this embodiment are the same as those in Embodiment 1. The difference is that in step S1, the mass ratio of Ketjen black, silicon oxide, aluminum silicate fiber, and magnesium zincate is 2:1:3.5:2.5. The rest is the same as in Embodiment 1.
[0094] Embodiment 15 Most of the steps in this embodiment are the same as those in Embodiment 1. The difference is that in step S1, in the quasi-solid electrolyte, there are 10 parts of quasi-solid matrix, 35 parts of alkaline compound, 3 parts of additive, and 52 parts of solvent. The rest is the same as in Embodiment 1.
[0095] Embodiment 16 Most of the steps in this embodiment are the same as those in Embodiment 1. The difference is that in step S1, the additives are Ketjen black and silicon oxide, and the mass ratio of Ketjen black and silicon oxide in the additives is 4:6. The rest is the same as in Embodiment 1.
[0096] Embodiment 17 Most of the steps in this embodiment are the same as those in Embodiment 1. The difference is that in step S1, the additives are aluminum silicate fiber and magnesium zincate, and the particle size of magnesium zincate is 280 - 300 mesh; the mass ratio of aluminum silicate fiber and magnesium zincate in the additives is 7:3. The rest is the same as in Embodiment 1.
[0097] Embodiment 18 Most steps of this embodiment are the same as those of Embodiment 1. The differences are as follows: in step S1, the additives are Ketjen black, aluminum silicate fiber and magnesium zincate, and the particle size of magnesium zincate is 280 - 300 mesh; in the additives, the mass ratio of Ketjen black, aluminum silicate fiber and magnesium zincate is 2.5:6:1.5. The rest is the same as that of Embodiment 1.
[0098] Embodiment 19 Most steps of this embodiment are the same as those of Embodiment 1. The differences are as follows: in step S1, the additives are Ketjen black, silicon oxide and magnesium zincate, and the particle size of magnesium zincate is 280 - 300 mesh; in the additives, the mass ratio of Ketjen black, silicon oxide and magnesium zincate is 1:8:1. The rest is the same as that of Embodiment 1.
[0099] Comparative Example 1 Most steps of this comparative example are the same as those of Embodiment 1. The differences are as follows: in step S1, the additive is Ketjen black, and the rest is the same as that of Embodiment 1.
[0100] Comparative Example 2 Most steps of this comparative example are the same as those of Embodiment 1. The differences are as follows: in step S1, the additive is silicon oxide, and the rest is the same as that of Embodiment 1.
[0101] Comparative Example 3 Most steps of this comparative example are the same as those of Embodiment 1. The differences are as follows: in step S1, the additive is aluminum silicate fiber, and the rest is the same as that of Embodiment 1.
[0102] Comparative Example 4 Most steps of this comparative example are the same as those of Embodiment 1. The differences are as follows: in step S1, the additive is magnesium zincate, and the rest is the same as that of Embodiment 1.
[0103] Comparative Example 5 Most steps of this embodiment are the same as those of Embodiment 1. The differences are as follows: in step S1, in the quasi-solid-state electrolyte, there is 1 part of additive.
[0104] Comparative Example 6 Most steps of this embodiment are the same as those of Embodiment 1. The differences are as follows: in step S1, in the quasi-solid-state electrolyte, there are 10 parts of additive.
[0105] Performance Test Ionic Conductivity of Quasi-Solid-State Electrolyte Test the ionic conductivity of the quasi-solid-state electrolytes obtained from the above embodiments and comparative examples, and the test results are shown in Table 1.
[0106] Perform the following battery performance tests on the nickel-zinc batteries obtained from the above embodiments and comparative examples.
[0107] 1) Internal Resistance Test Use an internal resistance tester to test the internal resistance of the nickel-zinc battery.
[0108] 2) Cycle life At 25 °C, charge the zinc-nickel batteries prepared in each example and comparative example at 1C to 1.9V and then charge at a constant voltage of 1.9V until the cut-off current is 13.5 mA, discharge at 1C to 1.3V, repeat the charge and discharge until the battery capacity drops to 60% of the first charge, and record the number of charge and discharge cycles. 3) High-temperature storage (1) Under the condition of 25 °C, charge the battery to full charge in a constant current and constant voltage charging mode, charge at 0.2C to 1.9V, and then charge at a constant voltage of 1.9V until the cut-off current is 13.5 mA to end the charging.
[0109] (2) Place the fully charged battery in an oven at 60 °C and store for 7 days.
[0110] (3) After the storage is completed, discharge at 0.2C to 1.3V, then charge using the same charging method as in (1), let it stand for 10 min, and then discharge at 0.2C to 1.3V, repeat the above charging and discharging steps 3 times.
[0111] Test the capacity retention rate after step (2) and test the capacity recovery rate after 3 times of the charging and discharging steps.
[0112] Table 1 It can be seen from the test results in Table 1 that when comparing Examples 1, 16-19 with Comparative Examples 1-4, the additive in Comparative Example 1 is a conductive agent. Although the obtained quasi-solid electrolyte has a high ionic conductivity and a low battery internal resistance, the high-temperature storage performance and cycle performance of the battery are poor; the additives in Comparative Examples 2-4 are insulating substances, fibers or zinc-containing substances, and the obtained batteries have a high internal resistance, poor cycle performance and poor high-temperature storage performance; it shows that the additive for the quasi-solid electrolyte of the nickel-zinc battery includes at least two or more kinds, the internal resistance of the battery is slightly lower, and the obtained battery has a high cycle life and storage performance.
[0113] When comparing Example 1 with Comparative Examples 5 and 6, the amount of the additive in Comparative Example 5 in the quasi-solid electrolyte is 1 part, and the amount of the additive is too small, resulting in a low cycle capacity retention rate and poor high-temperature performance of the battery; the amount of the additive in Comparative Example 6 is greater than 8 parts, which leads to too much additive in the solid electrolyte, which will reduce the conductivity, interfere with the electrode reaction, exacerbate self-discharge, weaken the thermal stability, and damage the performance of the nickel-zinc battery; it shows that the amount of the additive being 2-8 parts is helpful to improve the cycle performance and high-temperature storage performance of the battery.
[0114] Examples 1-4 change the types of conductive agent, insulating substance, fiber and zinc-containing substance, and the mass ratio of the conductive agent, insulating substance, fiber and zinc-containing substance is in the range of (1-2):(1-3):(1-3):(1-2). The obtained battery has good cycle performance and high-temperature storage performance, and the internal resistance of the battery is low.
[0115] Comparing Examples 1-4 with Examples 12-14, the additives in Examples 1-4 and Examples 12-14 are composed of four substances: conductive agent, insulating substance, fiber and zinc-containing substance. The mass ratio of the conductive agent, insulating substance, fiber and zinc-containing substance in Examples 12-14 is not in the range of (1-2):(1-3):(1-3):(1-2). The obtained quasi-solid electrolyte has a lower ionic conductivity, a higher battery internal resistance, and a poorer high-temperature storage performance of the battery. This shows that when the additive is composed of four substances: conductive agent, insulating substance, fiber and zinc-containing substance, and at the same time the mass ratio of the conductive agent, insulating substance, fiber and zinc-containing substance is in the range of (1-2):(1-3):(1-3):(1-2), the four additives can effectively interact with each other, more effectively reduce the negative electrode polarization, reduce the battery internal resistance, reduce the battery capacity attenuation, improve the battery cycle life, and improve the high-temperature storage performance of the battery. Comparing Examples 1, 5-6 with Examples 7, 8, it can be seen that when the thickness of the quasi-solid electrolyte is in the range of 0.5-2 mm, the obtained battery has a low internal resistance, good cycle performance, and good high-temperature storage capacity retention rate and capacity recovery rate.
[0116] Comparing Examples 1, 9-10 shows that the quasi-solid matrix including one or more of polyvinyl alcohol, sodium carboxymethyl cellulose, polyacrylic acid, and polyacrylamide can improve the battery cycle performance and high-temperature storage performance.
[0117] Comparing Examples 1, 16-17, 18-19 shows that the additive including two or more of conductive agent, insulating substance, fiber, and zinc-containing substance has the effects of improving the battery cycle performance, reducing the internal resistance, and improving the high-temperature storage performance of the battery.
[0118] The above examples are only used to illustrate the technical solutions of the present invention, not to limit it. Although the present invention has been described in detail with reference to the foregoing examples, those of ordinary skill in the art should understand that: they can still modify the technical solutions recorded in the foregoing examples, or perform equivalent replacements for some of the technical features. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the various embodiments of the present invention, and should all be included in the protection scope of the present invention.
Claims
1. A quasi-solid electrolyte for a nickel-zinc battery, characterized in that, Comprising the following parts by weight: 5 - 10 parts of quasi - solid matrix, 30 - 35 parts of alkaline compound, 2 - 8 parts of additive, and 57 - 63 parts of solvent, The additive includes two or more of conductive agent, insulating substance, fiber, and zinc - containing substance.
2. The quasi-solid electrolyte for nickel-zinc batteries according to claim 1, wherein The insulating substance includes one or more of silicon oxide, wollastonite, and asbestos.
3. The quasi-solid electrolyte for nickel-zinc batteries according to claim 1, characterized in that, The fiber includes one or more of aluminum silicate fiber, nylon 66 fiber, carbon fiber, acetate fiber, and polyvinyl alcohol fiber.
4. The quasi-solid electrolyte for nickel-zinc batteries according to claim 1, wherein The zinc - containing substance includes one or more of zinc oxide, magnesium zincate, zinc - copper alloy, zinc - magnesium alloy, and zinc - aluminum alloy.
5. The quasi-solid electrolyte for nickel-zinc batteries according to claim 4, characterized in that, The diameters of the zinc - copper alloy, the zinc - magnesium alloy, and the zinc - aluminum alloy are all 220 - 400 mesh.
6. The quasi-solid electrolyte for nickel-zinc batteries according to claim 1, characterized in that, The conductive agent includes one or more of Ketjen black, carbon black, graphene, carbon nanotubes, and graphite.
7. The quasi-solid electrolyte for nickel-zinc batteries according to claim 1, characterized in that, The thickness of the quasi - solid electrolyte is 0.5 - 2 mm; and / or, the ionic conductivity of the quasi - solid electrolyte is 50 - 120 mS / cm.
8. The quasi-solid electrolyte for nickel-zinc batteries according to claim 1, characterized in that, The additive is composed of a conductive agent, an insulating substance, a fiber, and a zinc - containing substance. In the additive, the mass ratio of the conductive agent, the insulating substance, the fiber, and the zinc - containing substance is (1 - 2):(1 - 3):(1 - 3):(1 - 2).
9. The quasi-solid electrolyte for nickel-zinc batteries according to claim 1, characterized in that, The quasi - solid matrix includes one or more of polyvinyl alcohol, sodium carboxymethyl cellulose, polyacrylic acid, and polyacrylamide; The alkaline compound includes one or more of KOH, NaOH, and LiOH; The solvent is deionized water.
10. A nickel-zinc battery, characterized in that, Comprising a positive electrode, a negative electrode, and the quasi - solid electrolyte according to any one of claims 1 - 9, and the quasi - solid electrolyte is disposed between the positive electrode and the negative electrode.